A complex adaptive system perspective of the green-restructuring of clusters - Ram Mohan Sasikumar Kamath (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2024)
Given the adverse efects of climate change (such as drought and fooding, damage to ecosystems and infrastructure, depletion of resources, deterioration of human health), society needs to transition to using sustainable systems of production and consumption. Regions and countries increasingly view the creation of green-clusters that can nurture green-innovation and spur new green-industries, as a solution to this challenge. In fact, the formation of green-clusters, and the greening of existing industrial clusters has been identifed as an important tool to achieving the GHG-reduction goals of the European Green Deal. However, Green-clusters need not be intrinsically sustainable. Especially when green-clusters are derived from existing clusters, they will inherit unsustainable processes. This means before these clusters can help regions and nations transition, they must themselves transition to greener products and production techniques. The green-restructuring of clusters has become a key area of interest to Evolutionary Economic Geography; and to the emerging feld of Geography of Transitions, which bridges Evolutionary Economic Geography and Sustainability-Transition Studies. However, owing to extant cluster-evolution frameworks' and cluster-evolution studies' inability to settle still ongoing discussions regarding the development of clusters, scholarship risks falling behind policymakers. This thesis contributes to the resolution of some of these discussions. Most importantly, we address the debate regarding the dynamics behind the process of clusters' green-restructuring. We then address debates regarding the role of place-based structures in shaping cluster-evolution, the role of agency in shaping cluster-evolution, the role of proximitydimensions in shaping the greening of clusters, and the multiscalar nature of cluster-evolution. – – Angesichts der negativen Auswirkungen des Klimawandels (wie Dürren und Überschwemmungen, Schäden an Ökosystemen und Infrastruktur, Erschöpfung der Ressourcen, Verschlechterung der menschlichen Gesundheit) muss die Gesellschaft zu nachhaltigen Produktions- und Verbrauchssystemen übergehen. Regionen und Länder sehen in der Schafung von grünen Clustern, die grüne Innovationen fördern und neue grüne Industrien anregen können, zunehmend eine Lösung für diese Herausforderung. Tatsächlich wurde die Bildung grüner Cluster und die Ökologisierung bestehender Industriecluster als ein wichtiges Instrument zur Erreichung der THG-Reduktionsziele des Europäischen Green Deal identifziert. Grüne Cluster müssen jedoch nicht zwangsläufg nachhaltig sein. Insbesondere wenn grüne Cluster aus bestehenden Clustern hervorgehen, werden sie nicht nachhaltige Prozesse übernehmen. Das bedeutet, dass diese Cluster, bevor sie Regionen und Nationen bei der Umstellung helfen können, selbst auf umweltfreundlichere Produkte und Produktionstechniken umstellen müssen. Die grüne Umstrukturierung von Clustern ist zu einem Schlüsselbereich von Interesse für evolutionäre Wirtschaftsgeographie und das neu entstehende Feld der "Geography of Transitions" geworden, das die evolutionäre Wirtschaftsgeographie und "SustainabilityTransition Studies" miteinander verbindet. Da die bestehenden Cluster-Evolutionsrahmen und Cluster-Evolutionsstudien jedoch nicht in der Lage sind, die immer noch andauernden Diskussionen über die Entwicklung von Clustern zu klären, besteht die Gefahr, dass die Wissenschaft hinter den politischen Entscheidungsträgern zurückbleibt. Die vorliegende Dissertation trägt zur Lösung einiger dieser Diskussionen bei. Vor allem befassen wir uns mit der Debatte über die Dynamik hinter dem Prozess der grünen Umstrukturierung von Clustern. Anschließend gehen wir auf Debatten über die Rolle ortsbezogener Strukturen bei der Gestaltung von Cluster-Evolutionen, die Rolle von Handlungskompetenz bei der Gestaltung von Cluster-Evolutionen, die Rolle von Nachbarschaftsdimensionen bei der Gestaltung der Ökologisierung von Clustern und die multiskalare Natur von Cluster-Evolutionen ein.
urn:nbn:de:gbv:3:2-1104114
Keywords: 330; Green-clusters; Agent-based modelling; Socio-technical transitions; Policy instruments; Bioeconomy